Coaching Clinic Penulisan Artikel Jurnal Bereputasi bagi Dosen Fakultas Ilmu Pendidikan Universitas Negeri Padang Tahap I - Muhammad Kristiawan; Muh. Sabir Mustafa Mustafa; Wawan Sopiyan; Badarudin Badarudin; Sri Fatmawati; Nova Asvio; Wahyu Nugroho (Lembaga Riset dan Inovasi Al-Matani, 2023)
The focus of this community service includes the ability of lecturers to write reputable journal articles. This community service aims to improve: 1) lecturers' understanding of writing good articles so that they can be published in reputable journals; 2) lecturer skills in writing good articles so that they can be published in reputable journals; and 3) awareness of lecturers about the importance of writing good articles so that they can be published in reputable journals. The methods used so that the purpose of this service can be carried out properly include: 1) coaching clinic through zoom meetings by providing some material about writing reputable journal articles; 2) Focus Group Discussion (FGD) on materials for writing articles in reputable journals; and 3) assisting in writing articles for reputable journals, tracing reputable journals and submitting articles that have been revised by the author from reviewers. This community service activity reveals the fact that: 1) the implementation of coaching clinic activities and discussions about writing reputable journal articles; 2) the implementation of mentoring activities for writing reputable journal articles; and 3) there is an increase in lecturers' knowledge in writing reputable journal articles. So that through this activity it is hoped that it will have positive implications in writing reputable journal articles for lecturers at the UNP Faculty of Education in particular and for lecturers from other faculties in general.